Ambient Intelligence - Software and Applications 2nd International Symposium on Ambient Intelligence (ISAmI 2011) - Novais, Paulo; Preuveneers, Davy.; Corchado, Juan M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
ISAmI is the International Symposium on Ambient Intelligence, and aims to bring together researchers from various disciplines that are interested in all aspects of Ambient Intelligence. The symposium provides a forum to present and discuss the latest results, innovative projects, new ideas and research directions, and to review current trends in this area. This volume presents the papers that have been accepted for the 2011 edition, both for the main event and workshop. The ISAmI workshop WoRIE promises to be a very interesting event that complements the regular program with an emerging topic on reliability of intelligent environments
AmI Support for the Trading Process: Self-Aware Trader Model -- Design time Methodology for the Formal Verification of Intelligent Domotic Environments -- Wheelchair-based system adapted to disabled people with very low mobility -- Toward Seamless Environments for Dispute Prevention and Resolution -- Integrating Personalized Health Care and Information Access for Elder People -- A DSL for Context Quality Modeling in Context-Aware Applications -- Non-intrusive Residential Electrical Consumption Traces -- Social Presence in Immersive 3D Virtual Learning AmI Environments -- A Digital Secretary for Smart Offices Setup Up -- Applying HoCCAC to Plan Task the COPD Patient: A Case Study -- Elder Care's Fall Detection System -- Multi-Agent System for Detecting Elderly People Falls Through Mobile Devices -- Intelligent Video Monitoring for Anomalous Event Detection -- Design and Modelling of the Nocturnal AAL Care System -- The EducAgent Platform: Intelligent Conversational Agents for E-Learning Applications -- Improving Human Face Detection through TOF Cameras for Ambient Intelligence Applications -- Recommendation and Planning through Mobile Devices in Tourism Context -- Mobile Personal Health Systems for Patient Self-management: On Pervasive Information Logging and Sharing within Social Networks -- Multi-Agent Strategy Synthesis in Smart Meeting Environments -- Reusable Gestures for Interacting with Ambient Displays in Unfamiliar Environments -- Graphs and Patterns for Context-Awareness -- ARTIZT: Applying Ambient Intelligence to a Museum Guide Scenario -- Reliability of Location Detection in Intelligent Environments -- Flexible Simulation of Ubiquitous Computing Environments -- Safety Considerations in the Development of Intelligent Environments -- LECOMP: Low Energy COnsumption Mesh Protocol in WSN -- A User-Friendly Interface for Rules Composition in Intelligent Environments -- Using an Ambient Intelligent Architecture for Developing an Intelligent Tutoring System for Training Operators of Power System Control Centres -- Ambient Intelligence Based Architecture for Immersive Social Entertainment -- Grouping Behaviour in AmI-Enabled Crowd Evacuation -- A Mobile System to Visualize Patterns of Everyday Life -- Human Behaviour Modelling Approach for Intention Recognition in Ambient Assisted Living -- Evolutionary Intelligence in Agent Modeling and Interoperability.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).